Bright investments: Measuring the impact of transport infrastructure using luminosity data in Haiti - Oscar A. Mitnik; Raul Sanchez; Patricia Ya\~nez-Pagans (Inter-American Development Bank (IDB), 2018)
This paper quantifies the impacts of transport infrastructure investments on economic activity in Haiti, proxied by satellite luminosity data. Our identification strategy exploits the differential timing of rehabilitation projects across various road segments of the primary road network. We combine multiple sources of non-traditional data and carefully address concerns related to unobserved heterogeneity. The results obtained across multiple specifications consistently indicate that receiving a road rehabilitation project leads to an increase in luminosity values between 7 percent and 15 percent at the communal section level. Taking into account the national level elasticity between luminosity values and GDP, we approximate that these interventions translate in GDP increases of around 0.6 percent and 1.2 percent in communal sections that were benefited by a transport project. Findings also uncover some temporal and spatial variation, showing that effects take some time to appear and that it is not the richest or the poorest communities that are gaining from these investments but those in the middle of the income distribution.
Keywords: O1; O47; R4; D04; 330; Haiti; night-time luminosity; road investments